2021
DOI: 10.1016/j.ultsonch.2021.105716
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and growth mechanism of micro spherical ammonium dinitramide crystal based on ultrasound-assisted solvent-antisolvent method

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Remarkably, four main crystal planes, i.e., (020), (121), (032), and (310) were detected for raw ADN. However, for ADN-0% MMT and ADN-1% MMT, the seven main crystal plane diffraction peaks were detected, which originated from the ADN crystal planes of (020), (011), (121), (031), (21-1), (040), and (032), respectively . Compared with raw ADN, the crystal plane (310) nearly disappeared, while the peak intensities of crystal planes (011), (031), (21-1), and (040) are remarkably strengthened in the XRD patterns of ADN-0% MMT and ADN-1% MMT.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Remarkably, four main crystal planes, i.e., (020), (121), (032), and (310) were detected for raw ADN. However, for ADN-0% MMT and ADN-1% MMT, the seven main crystal plane diffraction peaks were detected, which originated from the ADN crystal planes of (020), (011), (121), (031), (21-1), (040), and (032), respectively . Compared with raw ADN, the crystal plane (310) nearly disappeared, while the peak intensities of crystal planes (011), (031), (21-1), and (040) are remarkably strengthened in the XRD patterns of ADN-0% MMT and ADN-1% MMT.…”
Section: Resultsmentioning
confidence: 95%
“…However, for ADN-0% MMT and ADN-1% MMT, the seven main crystal plane diffraction peaks were detected, which originated from the ADN crystal planes of (020), (011), ( 121), ( 031), (21-1), (040), and (032), respectively. 26 Compared with raw ADN, the crystal plane (310) nearly disappeared, while the peak intensities of crystal planes (011), ( 031), (21-1), and (040) are remarkably strengthened in the XRD patterns of ADN-0% MMT and ADN-1% MMT. This indicates that the recrystallization in solvent-antisolvent (for ADN-0% MMT) changes the crystal characteristics of raw ADN, while the addition of MMT (for ADN-1% MMT) maintains the crystal characteristics of recrystallized ADN.…”
Section: ■ Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This is because different supersaturation levels caused by different cooling rates can change the selective adsorption of solute and solvent molecules on the crystal face, which is the key to controlling the crystal morphology of α-lactose. When Li et al 30 explored the growth mechanism of spherical ammonium dinitramide (ADN), they found that ADN crystals grew into large spheres based on the spiral growth model at low supersaturation, while they grew into small balls through rough growth at high supersaturation. Liu et al 31 studied the nano-confined crystallization of glycine in microemulsions (water/Triton X-100/n-hexanol/ cyclohexane).…”
Section: Supersaturation/supercooling Strategymentioning
confidence: 99%
“…[32][33][34] The synthesis methods of ADN include organic synthesis and inorganic synthesis, among which organic synthesis methods have not been developed on a large scale due to the drawbacks of low synthesis efficiency, complex synthesis routes, synthetic raw materials not being easily available, and not easy to be produced on a large scale. [35][36][37] The current means of ADN synthesis relies on inorganic methods, and the most common means is the separation and purication of crude ADN by using amino sulfonate as a raw material and nitrous sulfur mixed acid as a nitrifying agent under low temperature conditions, using ammonia to neutralize the product. [38][39][40][41] Amino sulfonates serve as key intermediates for the rapid formation of nitro functional groups.…”
Section: Introductionmentioning
confidence: 99%